Ψ, a Temperate Phage of Agrobacterium tumefaciens, Is Mutagenic - Expert, Dominique (1982)
A new temperate bacteriophage (phage Ψ) of Agrobacterium tumefaciens strain B91 is described. Many octopine-utilizing strains of A. tumefaciens harbor prophage Ψ or a phage that is similar if not identical to it. This phage has a very narrow host range, and we found that its growth is strongly reduced in strains which carry an octopine pTi plasmid. When sensitive bacteria are infected with Ψ, 1 to 3% of the survivors carry mutations on the chromosome, as well as on the pTi plasmid. This phenomenon appears to be a direct consequence of lysogenization. The possible mechanisms whereby such Ψ-induced mutations occur are discussed.